Neural mechanisms of swallowing and effects of taste and other stimuli on swallow initiation - Zakir, H.M. (2010)
Swallowing involves several motor processes such as bolus formation and intraoral transport of a food bolus (oral stage) and a series of visceral events that occur in a relatively fixed timed sequence but are to some degree modifiable (pharyngeal stage or swallow reflex). Reflecting the progressive aging of society, patients with swallowing disorders (i.e., dysphagia) are increasing. Therefore, there is expanding social demand for the development of better rehabilitation treatment of dysphagic patients. To date, many dysphagia diets have been developed and are available commercially to help bring back the pleasure of mealtimes to dysphagia patients. Texture modification of food to make the food bolus easier to swallow with less risk of aspiration is one of the important elements in dysphagia diets from the viewpoint of safety assurance. However, for the further development of dysphagia diets, new attempts based on new concepts are needed. One of the possible approaches is to develop dysphagia diets that facilitate swallow initiation. For this approach, an understanding of the mechanisms of swallow initiation and identification of factors that facilitate or suppress swallow initiation are important. In this review, we first summarize the neural mechanisms of swallowing and effects of taste and other inputs on swallow initiation based on data mainly obtained from experimental animals. Then we introduce a recently established technique for eliciting swallowing using electrical stimulation in humans and our ongoing studies using this technique.